The Levant: Reconciling a Century of Contradictions (American Journal of Islam and Society, 2012)
Although the revolution in Syria is unfolding within the country’smodern political borders, what is going on can only be understoodby placing it in a larger historical context, which includes the adjacentgeographical areas of Bilad al-Sham. Without such abroader view, the complexity of Syria’s current reality can neitherbe appreciated, nor can its consequences be accounted for and itsfuture anticipated.Probably in no country is the mess of a land’s colonial legacymore visible than it is in Syria. This legacy’s pathway marks thecountry’s future development, and its implications are facing therevolution today with arduous challenges. The resulting complexityextends beyond the political dimension, for a similar level ofcomplexity exists at the meta-cultural level as well. Furthermore,the change in Syria has regional consequences: It will institutionalizethe Arab revolution as an unavoidable political force and energizethe process of cultural reformation and the recovery of acivilizational Muslim identity.This essay first examines the region’s historical background andthe consequences of the Ottoman order’s disintegration. Second,it analyzes the national identity dilemmas faced by the Arab worldafter colonialism, how non-Muslims reacted to them, and the twopolitical paths that those countries pursued. Third, the essay discussesthe formation of grievances among Syrian minorities in particular. Fourth, the politics of the post-independence era arepresented, highlighting the promise of the development uponwhich Syria was embarking. The essay then investigates the politicsand social conditions that led to a dictatorship of three overlappingtypes: ideological left, sectarian, and neoliberal. Beforefocusing on the ongoing revolution, a note on Islamic activism ispresented due to the fact that Islamic meanings have always beenthe impetus propelling the people’s resistance. The revolutionaryrealities on the ground are then elaborated upon, emphasizing howthe regime’s extreme violence against peaceful protest intersectswith historical social alignments. Lastly, the essay discusses thegeopolitical context in which the Syrian revolution is taking place,which at once makes it hard to prevail and makes any of its outcomeshighly consequential for the whole region.